Unusual sesquiterpenes from Centaurea athoa DC. (March 2016) - Demir, Serdar; Karaalp, Canan; Bedir, Erdal
Graphical abstract: Highlights: Three new elemane-type sesquiterpenes were isolated from Centaura athoa DC. The isolated compounds were established by spectroscopic methods. A germacrane-type sesquiterpene is reported for the first time in the genus Centaurea . Abstract: Three new elemane-type sesquiterpenes; athoin, 14- O -acetylathoin and methyl 14- O -acetylathoin-12-oate were isolated from the aerial parts of Centaurea athoa DC., accompanying with eight known compounds: a germacrane-type sesquiterpene; 4'-hydroxypecterolide-14- O -acetate, three phenolic compounds; p -hydroxybenzoic acid, protocatechuic acid, vanillic acid-4- O -β-d -glucopyranoside methyl ester, an acetophenon glucoside; picein, two phenylpropane glucosides; syringin and 9- O -methyl coniferin, and a phytosterol; β-sitosterol-3- O -β-d -glucopyranoside. Structural elucidation of the compounds was based on both spectroscopic evidence and reference data comparison.